2006
DOI: 10.1111/j.1462-5822.2006.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal defences against orally acquired protozoan parasites, emphasis on Toxoplasma gondii infections

Abstract: SummaryProtozoan parasites that gain access to the host through the mucosal tissue of the alimentary tract may influence the development of intestinal inflammatory disorders. Despite the diversity of the extracellular and intracellular protozoan pathogens discussed in this review, our current understanding of the mechanisms involved in the immune response indicates that a common exuberant immune response to rid the host of these agents is elicited. This robust inflammatory response is orchestrated both by cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 61 publications
(62 reference statements)
1
57
0
8
Order By: Relevance
“…During the early phase, toxoplasmosis resistance is related to the initial production of IL-12 and IFN-γ by natural killer cells (Buzoni-Gatel et al 2006). During the chronic phase, TH1 CD4+ cells and CD8+ cytotoxic T lymphocytes are vital in producing protective immunity and long-term survival (Gazzinelli et al 1992).…”
mentioning
confidence: 99%
“…During the early phase, toxoplasmosis resistance is related to the initial production of IL-12 and IFN-γ by natural killer cells (Buzoni-Gatel et al 2006). During the chronic phase, TH1 CD4+ cells and CD8+ cytotoxic T lymphocytes are vital in producing protective immunity and long-term survival (Gazzinelli et al 1992).…”
mentioning
confidence: 99%
“…Le toxoplasme établit avec le système immunitaire de l'hôte un dialogue subtil [1] (Figure 2). Dès sa pénétration sous forme de tachyzoïte, Le chat, ou de façon plus générale les félidés, sont les seuls animaux dans lesquels le parasite effectue une reproduction sexuée, assurant un brassage chromosomique entre les souches.…”
Section: Subversion De L'immunité Par Le Parasiteunclassified
“…In mice infected with T. gondii, a population of NK cells that express activated CD44 emerges (39). Both IL-2 and IL-15 lead to the upregulation and activation of CD44, enhancing the ability of activated NK cells to produce IFN-γ (39,41). In addition, the pivotal role of NK cells in the induction of CD8 T cell immunity has been established in a murine model, even in the absence of CD4 T cells (47).…”
Section: Nk Cells and Parasitesmentioning
confidence: 99%
“…Adoptive transfer of CCR5 + / + NK cells into CCR5 -/ -mice restored their ability to survive lethal T. gondii infection, and demonstrated that CCR5 is required for NK cell homing into infected liver and spleen (35)(36)(37)(38). Recently, we found that BALB/c mice infected with E. granulosus respond by producing serum MCP-1 as early as 10 days post infection and we determined the serum MCP-1 and MIP-2 levels as indicators for the inflammatory process (39)(40)(41)(42). Other studies have demonstrated that mice infected orally with T. spiralis larvae develop quantitative and functional changes in the peritoneal macrophage population (43,44).…”
Section: Nk Cells and Parasitesmentioning
confidence: 99%
See 1 more Smart Citation